Seminal Vesicle Infection of Zinner Syndrome Misdiagnosed for Neoplasm - Young Joo Kim (Urogenital Tract Infection)
Zinner syndrome is a rare Müllerian duct congenital anomaly representing unilateral renal agenesis, ipsilateral seminal vesicle cyst, and ejaculatory duct obstruction. A 16-year-patient presented with dysuria, nocturia, and enduring diffuse perineal pain for two months. Radiologic studies revealed a right seminal vesicle cyst with a mass lesion and right renal agenesis. Ultrasonography guided transrectal biopsy indicated a seminal vesicle neoplasm. The mass was diagnosed as chronic inflammation. This paper reports a case of seminal vesicle inflammation associated with Zinner syndrome that was initially misdiagnosed as a neoplasm.